Physiological responses and energy expenditure to simulated epee fencing in elite female fencers - Bottoms, L.; Sinclair, J.; Gabrysz, T.; Szmatlan-Gabrysz, U.; Price, J. (Serbian Journal of Sports Sciences, 2011)
Understanding the physiological and energy expenditure responses required during the unique nature of fencing is important for the development of training/nutritional programmes for athletes involved in fencing. This study therefore examined the physiological responses of four elite female epee fencers during a simulated fencing task. Peak physiological measurements were determined during an incremental exercise test to exhaustion on a treadmill. In addition, oxygen consumption, heart rate and finger tip blood lactate samples were taken throughout a series of simulated fencing fights. The fencing fights consisted of 3 x 3 minutes of fencing, with 1 minute rest between each bout. The results demonstrated peak oxygen uptake (47±5 ml/kg•min-1) to be similar to that of other elite female fencers. High peak energy expenditures were elicited over short exercise durations (range 10.6-11.4 Kcal•min-1). Low blood lactate levels were evident and possibly due to the contribution of phosphocreatine for ATP regeneration.